Youth and high school sports coaches’ experience with and attitudes about concussion and access to athletic trainers by sport type and age of athlete coached() - Sarmiento, Kelly (J Safety Res, 2019)
INTRODUCTION: Concussions are a commonly reported injury in youth and high school sports and much of the responsibility related to concussion identification and response for young athletes is allocated to sports coaches. This paper presents findings on concussion-related education, access to resources, experiences, and attitudes among a large number of youth and high school sports coaches across a variety of sports nationwide. METHODOLOGY: Data were collected among coaches who completed the Centers for Disease Control and Prevention’s (CDC) HEADS UP online concussion training pre-test between November 2016 and November 2017. Coaches’ concussion-related education, access to resources, experiences, and attitudes were compared by age of athlete coached and level of contact of sport. Medium and large effect sizes were considered of practical significance for interpretation. RESULTS: During the study period, 187,801 youth sports or high school sports coaches completed the CDC HEADS UP online training and corresponding pre-test. Access to previous concussion training significantly varied among respondents by age of athlete coached. For example, 27.4% of coaches of athletes aged 5 and younger had taken previous training compared to 72.9% of coaches of athletes aged 14–18. About one-quarter (27.4%) of all coaches reported ever having had to pull an athlete out of a game because of a possible concussion and 19.5% reported access to an athletic trainer at all games and practices. These variables differed significantly among coaches by age of athletes coached; coaches of older athletes were more likely to report access to an athletic trainer and having had to pull an athlete out of a game compared to coaches of younger athletes. No statistical differences by level of contact were considered to be of practical significance based on effect size. CONCLUSION: Most coaches in this study report having access to education and hold attitudes consistent with best practices about concussion safety; however, overall access to concussion-related resources is limited. While differences in access to concussion-related education, experience, resources, and attitudes among coaches of varying levels of contact were small, medium to large variations were identified by age of athlete coached. PRACTICAL APPLICATIONS: Coaches bear an important part of the responsibility to prevent, identify, and manage concussions in young athletes. Tailored educational efforts may assist coaches of young athletes with recognition of concussion signs and symptoms and with feeling comfortable deciding whether an athlete needs to be evaluated for a possible concussion.